Genome-wide identification and expression analysis of IDD gene family in Gossypium hirsutum L - Shuo Zhang; Huixin Jiao; Dongyun Zuo; Qiaolian Wang; Limin Lv; Youping Zhang; Yi Yang; Guoli Song; Hailiang Cheng (Functional & Integrative Genomics, 2026)

Single-cell transcriptomic profiling identifies TIMP1 as a diagnostic marker linked to macrophage ferroptosis in ulcerative colitis - Wen-Hao Xiong; Shuo Huang; Yan-Hong Liu; Guo-Shan Chen; Dan-Zhou Li; Yong-Cheng Di; Wen-Bin Song; Yong-Chao Zhang; Yi-Fan Wang; Feng Qi (Tissue and Cell, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Dual-tailoring of microenvironment and electronic structure in tandem catalysts for highly selective CO2-to-ethanol electroreduction - Shuo Cui; Cheng Yang; Tingting Tang; Xinjie Liu; Xinlong Huang; Junyang Li; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2026)

SERS sensing platform based on MIL-100(Fe)@AgNPs for norepinephrine/adenosine monitoring in patient plasma - Peng Zhao; Kai Liu; Yueyan Li; Xiaofang Ban; Yuheng Wu; Jiaqi Liu; Xiaohong Wu; Ziyi Cheng; Fan Wang; Shuo Li; Feng Lin; Huifang Tang; et al. (Analytica Chimica Acta, 2026)

Prokaryotic Argonautes as programmable tools for foodborne biological hazards detection: mechanisms, applications, and prospects - Jing-bo Jiao; Cheng-long Zhao; Jiang-li Cao; Tong Lin; Qing Kang; Li-jun Wang; Nan Wang; Xin-jun Du; Shuo Wang (Critical Reviews in Food Science and Nutrition, 2026)

Synergistic analysis and vertical transport attribution of carbon monoxide surface concentrations and satellite column loadings over China - Shuo Wang; Jason Blake Cohen; Kai Qin; Luoyao Guan; Pravash Tiwari; Ye Feng; Xiaolu Li; Qin He; Zhengqiang Li; Cheng Fan; Dacheng Wang (Remote Sensing of Environment, 2026)

Mussel-inspired construction of superhydrophilic/underwater superoleophobic PTFE membranes using a novel ε-polylysine-based modification for efficient oil-water separation - Xin Wu; Chenyang Li; Shuiling Hong; Ang Gao; Haoming Duan; Wei Li; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Synergistic TP/APTES coating on PBT membrane enables superhydrophilicity and efficient oil-water separation - Shuiling Hong; Chenyang Li; Xin Wu; Ang Gao; Haoming Duan; Man Liu; Sijia Zhang; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Royal jelly enhances ovarian function by modulating taurocholic acid metabolism and attenuating oxidative stress in D-galactose-induced POI mice - Xiaoxue Zheng; Peihao Sun; Changjiu He; Mingxiao Liu; Jieruo Qiu; Zhiming Ding; Yingying Zhang; Shuo Zhou; Ji Zhou; Jingzhe Sun; Wenwen Feng; Lu Zhang; et al. (Food Research International, 2026)

Process-dependent structural and functional modification of yeast protein: Alkaline extraction-acid precipitation versus high-pressure homogenization-assisted pH shifting - Lin Li; Xiaoyu Ma; Dan Huang; Ming Du; Shuo Wan; Shuzhen Cheng (Food Chemistry, 2026)

Synthesis of nitrogen-doped citric acid carbon dots and their applications in chitosan-based antimicrobial coatings for blueberry preservation - Xiaoyun Ma; Chuanxiang Cheng; Yujie Lei; Shuo Yuan; Yuwan Luo; Yongjin Qiao; Tiantian Min; Jin Yue (Food Chemistry, 2026)

Straw return enhances soil multifunctionality and maize yield through shifts in bacterial community structure - Shijie Deng; Yang Yu; Yubo Hao; Yubo Jiang; Guoyi Lv; Yiteng Zhang; Linjing Han; Meng Cheng; Shuo Zhang; Chunrong Qian (Field Crops Research, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

Hydro-mechanical behavior and modeling of fouled ballast under coupled water immersion and cyclic loading - Zhihao Yang; Hengwen Liu; Huaiping Feng; Shiao Cheng; Shuo Dong; Deliang Ma; Shuaijie Guo (Transportation Geotechnics, 2026)

Future climate and land-use change reshape watershed best management practices portfolio for nutrient control - Yuanxin Ren; Hangzhen Zhang; Shuo Cheng; Bingqian Liu; Lin Ji; Jun Xia; Dandong Cheng (Journal of Hydrology, 2026)

An integrated sensing, adsorption, and recovery platform using engineered Escherichia coli for mercury remediation - Mingzhu Huang; Li Kong; Yanzi Huang; Shuo Gao; Hao Cheng; Xuelan Chen (Environmental Research, 2026)

Dynamic failure characteristics of coral reef limestone with inclined growth lines: insights from DEM–FDM coupled SHPB simulations - Shao-shuo Li; Cheng Chen (Computers and Geotechnics, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Active far-to-close perception via optimal fishbone-view estimation for robotic truss tomato harvesting - Hefei Luo; Liang Gong; Shuo Zhang; Cheng Luo; Ziye Zhang; Feifan Wu; Zongxiao Li; Yangtian Lin; Chengjin Qin; Chengliang Liu (Computers and Electronics in Agriculture, 2026)

Chloride-repelling and interfacial hydroxyl enrichment synergy in Co-Pi@Cr2O3-CoP for high current density alkaline seawater electrolysis - Tingting Tang; Cheng Yang; Xinlong Huang; Shuo Cui; Xinjie Liu; Junyang Li; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2026)

Gravity-assisted dual-mode biosensor based on CbAgo-driven gel-sol transition of DNA hydrogels for Salmonella detection - Jing-bo Jiao; Cheng-long Zhao; Bei-bei Tian; Jiang-li Cao; Qing Kang; Li-jun Wang; Nan Wang; Xin-jun Du; Shuo Wang (Chemical Engineering Journal, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Tire wear particle and leachate induce oxidative stress and reshape the rice rhizosphere soil system: Multi-omics evidence of tissue-specific phytotoxicity - Snehal Wasnik; Shuo Cheng; Xiaoli Zhao; Kimleng Keang; Haoge Zhang; Jeffrey S. Cross (Journal of Hazardous Materials, 2026)

Quantitative assessment of the resource recovery potential from end-of-life lead-acid batteries based on consumption patterns: A case study from China - Huimin Hou; Wei Wei; Sui Zhang; Shuo Zhu; Zichen Di; Fangqin Cheng; He Xu; Junli Liu (Environmental Impact Assessment Review, 2026)

An automated and portable magnetically-controlled microfluidic chip platform with dual detection modes for sensitive AFP quantification - Peng Zhang; Chenqi Zhang; Min Jia; Yongdong Pan; Shuo Wu; Jianxin Cheng; Lujie Song; Zizhen Ming (Analytica Chimica Acta, 2026)

Genesis of the Zhamuqin Pb−Zn−Ag polymetallic deposit in the middle-southern Great Xing’an Range, NE China: constraints from H−O−S−Pb isotope geochemistry and geochronology - Peng He; Man Li; Shuo Guo; Fei Teng; Xianyu Cheng; Qilong Fu (International Geology Review, 2026)

Synthesis of visible-light-responsive magnetic recyclable ternary photocatalyst g-C3N4/Bi2O3/Fe3O4 for heavy metal stabilization from municipal solid waste incineration fly ash - Quanming Ren; Zunchao Ren; Feng Lin; Qingsong Zhang; Shuo Feng; Fei Cheng (Journal of Environmental Chemical Engineering, 2026)

Electrospinning of myoglobin incorporated polyvinyl alcohol/pullulan film as intelligent freshness indicator: Fabrication, characterization and indicating salmon freshness - Yushan Zhang; Yujie Lei; Chuanxiang Cheng; Xiaoyun Ma; Shuo Yuan; Yuwan Luo; Libing Liu; Tiantian Min; Jin Yue (Food Packaging and Shelf Life, 2026)

Ultrahigh-holmium carbon dots enable single-element-mediated dual-modality CT/MR imaging in vivo - Nan Liu; Ke Xiang; Tiantian Guo; Shuo Li; Qiyu Sun; Jinbin Pan; Ran Cheng; Dingbin Liu; Cai Zhang; Gang Shu; Shao-Kai Sun (Chemical Engineering Journal, 2026)

Exploratory observation of dietary exogenous bile acids on growth, hepatic glucose metabolism, intestinal and liver health, and fillet quality of Monopterus albus fed high-carbohydrate diets - Jiamin Li; Peng Fang; Ao Luo; Luyao Xu; Tianlun Luo; Junzhang Han; Tingting Li; Xiaoxuan Qi; Shuo Cheng; Huanhuan Huo; Mo Peng (Animal Feed Science and Technology, 2026)

Triterpenoid saponins from Caragana korshinskii Kom.: α ‑glucosidase inhibitory activity and characterisation of four new compounds - Yumei Ma; Tao Chen; Zhibo Song; Hailun Feng; Defa Kong; Juyuan Luo; Shuo Wang; Cheng Shen; Yulin Li (Natural Product Research, 2026)

Molecular networking-assisted isolation, structural elucidation, and bioactivity evaluation of new diterpenoids from Chaetocarpus castanocarpus - Chutipong Auntarn; Chaisak Chansriniyom; Ho-Cheng Wu; Hsun-Shuo Chang; Jiranuch Mingmuang; Sariyarach Thanasansurapong; Rutt Suttisri; Suchada Sukrong; Supakarn Chamni (Natural Product Research, 2026)

Auxin is a signal for algal-bacterial inter-kingdom interactions in marine diatom algal blooms - Xinyang Li; Xueyu Cheng; Mengjie Wu; Shuo Han; Xiaobing Wen; Si Tang; Zhonghua Cai; Jin Zhou (Journal of Hazardous Materials, 2026)

Functional diversity and catalytic preference of novel thermophilic catechol 2,3-dioxygenase for the biodegradation of aromatic pollutants - Yalin Yin; Shuxin Su; Shenmei Sun; Hengchao Zhu; Shuo Cheng; Ya Bian; Yue Yang; Jingjing Zhang; Jingjing Liu; Wei Wang (International Biodeterioration & Biodegradation, 2026)

Self-catalyzed NiFe foam anode fabricated via tape-casting for oxygen evolution reaction in anion exchange membrane water electrolysis - Li-Da Chiu; Calvin Leo Putra; Shuo-En Yu; I-Chung Cheng; I-Chih Ni; Chih-I Wu; I-Chun Cheng; Jian-Zhang Chen (Fuel, 2026)

The interface regulation strategy constructing high performance C3H6/C3H8 separation membranes via bio-based polyphenols - Dacheng Zhang; Qian Zhang; Ningning Gao; Leixin Yang; Yuchao Ma; Hang Li; Zhanfeng Zhao; Junkui Gao; Kaihua Li; Shuo Yang; Dengkun Shu; Huiguo Wang; et al. (Chemical Engineering Journal, 2026)

New nor-tirucallane triterpenoid with antitumor activity from Ailanthus altissima (mill.) swingle - Can Liu; Jun-ling Guo; Shuo-yu Zhao; Ning-ning Shi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

SsWOX13, a novel sugarcane WOX transcription factor, confers disease resistance via HR-mediated programmed cell death in Nicotiana benthamiana: Insights from a genome-wide survey - Farhan Goher; Faiza Shafique Khan; Shuo-Hang Zhang; Shengren Sun; Wei Zhang; Yinjie Cheng; Qinnan Wang (Plant Science, 2026)

Hydrogen adsorption and transport in clay-rich geomaterials: Implications for large-volume underground hydrogen storage - Shuo Wang; Yifeng Wang; Tuan A. Ho; Yuntian Teng; Meng Ji; Mohammad Goli; Cheng Chen (Fuel, 2026)

Co-exposure to microplastics and tire particles exacerbates oxidative stress and gut microbiome dysbiosis in zebrafish (Danio rerio) - Kimleng Keang; Shuo Cheng; Xiaoli Zhao; Snehal Wasnik; Haoge Zhang; Jeffrey S. Cross (Environmental Research, 2026)

Genome-Wide Identification and Expression Analysis of EBP Genes in Cotton - Lingyu Hao; Dongyun Zuo; Qiaolian Wang; Limin Lv; Youping Zhang; Yi Yang; Xue Zhang; Shuo Zhang; Guoli Song; Hailiang Cheng (Biochemical Genetics, 2026)

Identification of tire and road wear particles in artificial water bodies in Japan - Kimleng Keang; Shuo Cheng; Snehal Wasnik; Haoge Zhang; Jeffrey S. Cross (Chemosphere, 2026)

Mechanisms of phosphorus release from coastal sediments driven by organic matter enrichment at high nitrogen concentrations - Chun-Pu Zhao; An-Hao Wang; Ying Zeng; Wen-Hao Yin; Cheng Luo; Shi-Xia Liu; Miao Liu; Hai-Jun Wang; Xiao-Wen Li; Ji-Lin Xu; Shuo-Nan Ma (Marine Pollution Bulletin, 2026)

Heterologous overexpression of apple MdWAPL1 promotes fruit shape and alters fruit quality in tomato - Wenyun Shen; Pengda Cheng; Xiaomei Li; Zhiyu Zheng; Shuo Zhang; Fang Ma; Abid Khan; Xinyue Yang; Zhongxing Li; Yutian Zhang; Fengwang Ma; Chundong Niu; et al. (Plant Science, 2026)

Phosphorus‑nitrogen synergistic flame retardancy in lyocell fiber composites: Mechanistic investigation - Chunzu Cheng; Qingbo Zhao; Zhongkai Xu; Min Gao; Dong Zhang; Jia Shi; Shuo Yang; Jigang Xu; Bowen Cheng (Carbohydrate Polymers, 2026)

Numerical and experimental studies on the flow field of a semi-submersible aquaculture platform - Kai Wang; Yi-Han Wen; Jia-Ming Liu; Cheng Liang; Shuo Huang (Aquacultural Engineering, 2026)

A deep learning approach predicts O3 increase and PM2.5 declines under high emission scenario across the Northern China urban agglomeration - Gangfeng Zhang; Shuo Wang; Jing Xu; Tim R. McVicar; Yun Cheng; Cesar Azorin-Molina; Lorenzo Minola; Nan Wang; Jiang Zhang; Peijun Shi (Urban Climate, 2026)

Mid-holocene environmental changes and glacial-isostatic uplift recorded in a coastal isolation basin on inexpressible Island, Ross Sea, Antarctica - Shuo Wang; Yuzhu Zhang; Ninglian Wang; Zhiheng Du; Yan Zhu; Peng Cheng; Yuda Chui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

An integrated engineered microbial system for copper biosorption, real-time monitoring, and magnetic recovery in water remediation - Mingzhu Huang; Yanzi Huang; Xindong Yang; Wenxin Liu; Li Kong; Shuo Gao; Hao Cheng; Xuelan Chen (Bioresource Technology, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Impact of tire particles and tire leachate contaminants on plant physiology and soil health: Case study in mung bean and tomato - Snehal Wasnik; Shuo Cheng; Kimleng Keang; Haoge Zhang; Jeffrey S. Cross (NanoImpact, 2026)

Analysis of the efficient and stable organic matter removal performance and microbial community in a two-stage A/O-MBBR pilot-scale system - Shuo Li; Xiaowan Dong; Juntao Cheng; Fangshu Wang; Liyan Wang; Xifeng Zhao; Shuoyang Wang; Guosheng Wang; Qingyang Bi; Reng Zhang; Dong Chen (Journal of Water Process Engineering, 2026)

Hydrothermal extraction and characterization of hemicellulose from biomass as a natural emulsifier - Yilin Li; Shuo Jiang; Zhiyuan Xu; Yixiang Xu; Seunghee Yoon; Xuanbo Liu; Yifan Cheng; Sean F. O'Keefe; Jactone Ogejo; Feng Lin; Yiming Feng; Haibo Huang (Food Chemistry, 2026)

The p -JNKThr183/Tyr185 / p -Keap1Thr43 /Keap1 axis mediates arsenic-induced endothelial dysfunction by coordinating Chaperone-mediated autophagy with macroautophagy - Jinyu Li; Jin Cheng; Zhihan Yang; Lin Gao; Qiaoling Liu; Jing He; Yishan Dong; Shuo Wang; Jing Cui; Ziqi Xu; Dianjun Sun; Wei Zhang (Chemico-Biological Interactions, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Ecological characteristics and carrying capacity analysis of marine ranching ecosystem in Beibu Gulf based on Ecopath model - Cheng Cheng; Haolin Yu; Jie Feng; Yan Li; Qingxian Cao; Li Liu; Cheng Yang; Shan Zhao; Shuo Li; Zhen Zhang; Haiyan Wang; Tao Zhang (Journal of Oceanology and Limnology, 2026)

Divergent occupational heat stress strategies required for Northern and Southern China under climate change - Zhengyuan Liu; Wei Liu; Shuo Wang; Xiuquan Wang; Jinxin Zhu; Dagang Wang; Cong Dong; Guanhui Cheng; Yiwen Mei; Xiaoxing Qi (International Journal of Biometeorology, 2026)

Evaluation of quinazolin-4(3H)-one derivatives containing the bioactive acetohydrazide group as fungicidal candidates - Wenfei Zhang; Jiacheng Liu; Sifei Qi; Zihan Li; Yiwen Chen; Yufei Gong; Xiangkun Luo; Shuo Wang; Feng Liu; Yu-Cheng Gu; Xuewen Hua (Pesticide Biochemistry and Physiology, 2025)

Microalgae-derived carbon quantum dots enhance photosynthesis and accumulation of energy storage compounds in microalgal communities - Zhang Haoge; Cheng Shuo; Wasnik Snehal; Keang Kimleng; Jeffrey S. Cross (Journal of Environmental Chemical Engineering, 2025)

Production of cellulose nanocrystals from waste Phellinus igniarius substrate by enzymatic hydrolysis-centrifugal fractionation method: Construction of a bioactive substance delivery system - Shuo Zhang; Shuang Guo; Jiayu Han; Zhaolian Han; Hailing Yu; Xue Zhang; Ningcan Ma; Zhiqiang Cheng (Food Research International, 2025)

Investigation of the structure-activity relationship of resveratrol and its glycosylated and acylated derivatives in relation to their α-glucosidase inhibitory activities - Changdong Lin; Juyuan Luo; Shuo Wang; Cheng Shen; Shucan Zhang; Zhibo Song; Yumei Ma; Yongling Liu; Yulin Li; Tao Chen (Food Chemistry, 2025)

High-performance antifouling electrochemical aptsensor based on a Y-shaped glycopeptide and platinum nanoparticles for detecting aflatoxin B1 in food - Cheng Zhang; Xujun Pu; Xian Chen; Jinzhi Liang; Kun Ge; Yangyue Ding; Lunzhao Yi; Ying Gu; Shuo Wang (Food Chemistry, 2025)

Mechanical performance of an assembled 3D auxetic hybrid structure under eccentric and axial compression - Jia Shuo Liu; Yi Zhang; Xiang Jie Wei; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Tao Ding; Jia Hui Zhang; Lin Hua; Tong Cheng; Xin Ren (Engineering Structures, 2025)

Enhancing NO sensing performance using a bismuth-doping strategy for Yttria-stabilized zirconia-based electrochemical sensors - Hongqian Sun; Jing Song; Congcong Zhao; Shuo Tian; Zhenqian Cheng; Liangliang Tian; Tao Qi (Chemical Engineering Journal, 2025)

Nanozyme-mediated drug ion-exchange strategy ameliorates inflammatory bowel disease by scavenging ROS and reprogramming proinflammatory macrophages - Hongyan Lu; Ying Cheng; Xiangling Pu; Xingtao Zhao; Ruolan Li; Ruiqi Sun; Xiaoman Xie; Mingyue Wu; Shuo Zhang; Qiong Pan; Jin Chai (Chemical Engineering Journal, 2025)

Genome-wide identification and functional annotation of the ascorbate peroxidase (APX) gene family in cotton: putative roles in reactive oxygen species (ROS) homeostasis within pigment glands - Xue Zhang; Dongyun Zuo; Qiaolian Wang; Limin Lv; Youping Zhang; Yi Yang; Lingyu Hao; Shuo Zhang; Guoli Song; Hailiang Cheng (Planta, 2025)

Novel insights into quorum-sensing microbe combined with dimethylsulfoniopropionate enhancing bioremediation of oil-contaminated sediment under typical deep-sea conditions: The performances and molecular mechanisms - Shugang Hu; Shijie Li; Lingzhe Wang; Shuo Wang; Dongle Cheng; Jianliang Xue; Yu Gao; Siheng Lin; Chengbo Li; Yanlu Qiao; Yuyang Liu (Marine Pollution Bulletin, 2025)

From innovation to sustainability: How does the birth of innovative enterprises affect urban carbon emission intensity in China? - Tianheng Shu; Xia Liao; Shuo Yang; Guangyu Cheng; Taofang Yu (Sustainable Cities and Society, 2025)

Combined effect of microplastics and tire particles on Daphnia magna: Insights from physiological and transcriptomic responses - Kimleng Keang; Sovannlaksmy Sorn; Shuo Cheng; Snehal Wasnik; Haoge Zhang; Jeffrey S. Cross (Environmental Pollution, 2025)

Research on the Meso-mechanism of the Evolution of Wet Expansion Cracks in Expansive Soil Based on Discrete Element Method - Xue-lei Cheng; Xiao-fan Xing; Sheng-hui Feng; Shuo-shuo Guo; Qi-qi Li; Lu-yun Guo; Zhong-hao Zhu (Applied Geophysics, 2025)

Parametric dynamic responses analyses of subway station structure surrounded by saturated soft interlayer - Xue-lei Cheng; Sheng-hui Feng; Shuo-shuo Guo; Xiao-fan Xing; Lu-yun Guo; Zhong-yu Zhu (Applied Geophysics, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Nitrogen addition decouples the microbial necro-mass from soil organic carbon formation in a temperate grassland - Huanhuan Cheng; Yingbin Li; Shuo Li; Tianran Sun; Guoxiang Niu; Qi Li; Junjie Yang; Yanxia Ma; Yingzhi Gao; Qiang Yu; Haitao Zhao; Qiushi Ning; et al. (Journal of Environmental Sciences, 2025)

Antifouling electrochemical aptasensor based on a polyzwitterion copolymer for analyzing aflatoxin B1 in food - Meirong Niu; Xujun Pu; Xian Chen; Dabing Ren; Cheng Zhang; Lunzhao Yi; Yukun Yang; Ying Gu; Shuo Wang (Food Chemistry, 2025)

Effect of 7-O-glycosyl acylation of flavonoids from barley seedlings on α-glucosidase inhibition - Tao Chen; Changdong Lin; Weihang Lu; Shuo Wang; Cheng Shen; Juyuan Luo; Yulin Li (Food Chemistry, 2025)

Research on a method of generating future meteorological parameters for building HVAC design - Chen Cheng; Xiaoyi Fang; Mingcai Li; Jing He; Yaning Gao; Shuo Zhang; Ying Yu (Energy and Buildings, 2025)

Simultaneously enhancing sludge indirect drying and inhibiting hydrogen sulfide and ammonia gas emission by heat-activated persulfate oxidation - Dexiao Ma; Shuo Cheng; Guozhao Ji; Aimin Li (Chemical Engineering Journal, 2025)

Spatial–Temporal Dynamics of Drought Characteristics and Its Influencing Factors on Tibetan Plateau - Zhizhu Zhou; Wenjun Yu; Lin Zhao; Yanzhong Li; Shuo Cheng; Jiazhe Duan; Yincong Xing; Wei Shao (International Journal of Climatology, 2025)
Assessing drought on the Tibetan Plateau (TP) is essential for understanding the spatial characteristics of the region's hydrological regimes, as well as the trends of the evolving climate‐ecological system. Based on the precipitation and the potential evapotranspiration data from the ERA5‐Land dataset, this study evaluated the drought characteristics on the TP from 1950 to 2022 using the Standardised Precipitation Evapotranspiration Index (SPEI) and the Run theory. The analysis of SPEI at multiple time scales—SPEI‐1 (monthly), SPEI‐3 (seasonal), and SPEI‐12 (annual)—consistently revealed a pronounced drying trend across the TP over the past 70 years. Notably, the wet‐to‐dry transition points were detected in 2000 and 2001 based on the SPEI‐1 and SPEI‐3 series, respectively, while the SPEI‐12 series indicated a later shift occurring in 2004. In addition, the SPEI values indicated a spatial trend of increasingly severe drought conditions from south to north. Particularly, pronounced drought stress was observed in the Brahmaputra, Ganges, and Indus basins, as well as in the southern regions of the Inner Plateau. Furthermore, the relationships between drought variability and key climatic drivers—including sunspots, El Niño‐Southern Oscillation (ENSO), temperature (TEMP), and annual mean areal precipitation (AP)—were identified through cross‐wavelet transform (XWT) and wavelet coherence analysis (WTC). In general, the analysis showed that the SPEI values on the TP were negatively correlated to ENSO and TEMP but positively correlated to sunspots and AP. This study offers a comprehensive spatiotemporal assessment of drought dynamics across the TP, providing critical insights for regional water resource management and climate change adaptation planning.

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Training of mesenchymal stem cells by using hydrogel microspheres for the repair of intervertebral disc degeneration - Mingzheng Chang; Xiaohui Zhang; Xiaoxiong Wang; Qingliang Ma; Shangye Li; Cheng Qiu; Shuo Wang; Suomao Yuan; Yonghao Tian; Yunhao You; Dapeng Zhang; Jiwei Cui; et al. (Chemical Engineering Journal, 2025)

Hypoxia-preconditioned ADSC exosomes encapsulated in a multifunctional dual-network hydrogel promote the healing and functional regeneration of seawater-immersed wounds - Jie Li; Zishuo Wang; Wenjing Yang; Yongchao Zhou; Tao Fu; Yuhui Zhang; Xuzhou Duan; Dong Liu; Lingtong Kong; Yan Shang; Yuchen Zhang; Xuhui Wang; et al. (Chemical Engineering Journal, 2025)

Development and application of a real-time fluorescent RAA assay for H9 subtype avian influenza viruses - Wanting Zhou; Xiaoqi Li; Jie Tian; Shuo Liu; Cheng Peng; Jinping Li; Guangyu Hou; Jizhe Yang; Wenming Jiang; Hualei Liu (Virus Genes, 2025)

Advancements in the investigation of the mechanisms underlying cognitive aging - Honglu Zou; Shuo Zhang; Xinxin Cui; Hongyan Xu; Zhangying Zhou; Danmeng Cheng; Yanan Han; Youcai Tang; Anqin Dong; Xianwen Dong (Biogerontology, 2025)

Discrete element calculation model and parameter sensitivity analysis of expansive soil - Xue-lei Cheng; Shuo-shuo Guo; Wei-jian Liu; Qi-qi Li; Ran Hai (Applied Geophysics, 2025)

Organic fertilizer mitigated the oxidative stress of tomato induced by nanoplastics through affecting rhizosphere soil microorganisms and bacteriophage functions - Liang-Bin Zhao; Zi-Xuan Tang; Hui-Fang Zhai; Hong-Yu Lai; Hai-Yang Li; Shuo Liu; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Better ecosystem resistibility but with severer risk deriving from potential pathogens and antibiotic resistances in marine sediments adjacent to Yellow River estuary under oil contamination - Yanlu Qiao; Mingan Shen; Lingbing Kong; Yudi Sun; Shuo Wang; Yu Gao; Jianliang Xue; Qing Jiang; Dongle Cheng; Yuyang Liu (Environmental Research, 2025)

Experimental testing and machine learning to predict the load-slip behavior of stud connectors in steel-UHPC composite structures - Yong-jian Zhou; Xia Yang; Wu-wu Zou; Cheng-shuo Han (Engineering Structures, 2025)

From soft to hard adventure: Examining experienced mountaineers’ mountaineering intentions through the lens of the theory of planned behavior - Shih-Shuo Yeh; Tai-Ying Chiang; Kuan-Ying Chen; Chen-Lin Lee; Tzung-Cheng Huan (Journal of Outdoor Recreation and Tourism, 2025)

A spatiotemporal mixed-enhanced generative adversarial network for radar-based precipitation nowcasting - Long He; Kun Zheng; Huihua Ruan; Shuo Yang; Jinbiao Zhang; Cong Luo; Siyu Tang; Yunlei Yi; Yugang Tian; Jianmei Cheng (Computers & Geosciences, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Digital Guide and Handheld Robot-Assisted Tibial Tunnel Placement in Anterior Cruciate Ligament Reconstruction: A Cadaver Study - Hao-Cheng Zuo; Ping-Lang Yen.; Shuo-Suei Hung (Journal of Medical and Biological Engineering, 2025)

Tempestites in the marine environment: review and perspectives - Shuo Feng; Chenlin Hu; Xin Li; Wenxuan Sun; Jonathan Atuquaye Quaye; Hongmei Su; Cheng Dong (International Geology Review, 2025)

Intricate relationship among major heat-induced harmful by-products and modulating role of lipid and protein oxidation in seafood: A comprehensive review - Huaixu Wang; Baoping Shi; Zening Zhang; Lingling Zhao; Haixia Xiong; Shuo Han; Qi Wang; Ka-Wing Cheng (Food Research International, 2025)

Prediction of Pharmacoresistance in Drug-Naïve Temporal Lobe Epilepsy Using Ictal EEGs Based on Convolutional Neural Network - Yiwei Gong; Zheng Zhang; Yuanzhi Yang; Shuo Zhang; Ruifeng Zheng; Xin Li; Xiaoyun Qiu; Yang Zheng; Shuang Wang; Wenyu Liu; Fan Fei; Heming Cheng; et al. (Neuroscience Bulletin, 2025)

Self-powered multisensory neuromorphic device with auditory and rotational perception integration inspired by the labyrinth of the inner ear - Feiyu Wang; Jia-Han Zhang; Shuo Ke; Jiean Li; Fengchang Huang; Wen Cheng; Yi Shi; Lijia Pan (Chemical Engineering Journal, 2025)

Inflammation May Mediate the Effects of Fluoride on Liver and Kidney Function of Adults: Cross-Sectional Studies in China - Minghao Geng; Yi Cheng; Leizhen Duan; Guangshen Dong; Shuo Yang; Xuecheng Jiao; Weihua Jia; Hui Huang; Ming Dou; Xiaoli Fu; Fangfang Yu; Yuhui Du; et al. (Biological Trace Element Research, 2025)

Enhancement of bioremediation efficacy in petroleum-contaminated marine environments via Quorum sensing: Mechanistic insights and efficacy - Jianliang Xue; Yue Dun; Shuo Wang; Dongle Cheng; Yanlu Qiao; Yuyang Liu; Feng Wang; Xiaoya Zhang; Yanan Li (Journal of Environmental Chemical Engineering, 2025)

Mechanism of sodium alginate synergistically improving foaming properties of pea protein isolate: Air/water interface microstructure and rheological properties - Yanan Guo; Shuo Zhang; Yue Gu; Tianfu Cheng; Fuwei Sun; Yichang Wang; Daoying Wang; Zhongjiang Wang; Zengwang Guo (Food Hydrocolloids, 2025)

Harnessing the polysaccharide production potential to optimize and expand the application of probiotics - Dong-Xu Ma; Hui-Juan Cheng; Hui Zhang; Shuo Wang; Xiao-Tao Shi; Xin Wang; Da-Chun Gong (Carbohydrate Polymers, 2025)

Establishment and application of a duplex fluorescent quantitative PCR assay for H9N2 subtype avian influenza virus and infectious bronchitis virus - Wanting Zhou; Qiuyan Mao; Shuning Zhou; Tingting Li; Jie Tian; Xiaoqi Li; Shuo Liu; Cheng Peng; Zhibin Hu; Jinping Li; Guangyu Hou; Houhui Song; et al. (Virus Genes, 2025)

Evaluation on the antiviral activity of luteolin against largemouth bass virus - Guang-shuo Wang; Jia-cheng Qin; Yun-long Qin; Yao Wang; Bin Yang; Xiang Liu; Fei Ling; Gao-xue Wang (Aquaculture, 2025)

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

Construction of novel quaternary ammonium nitroxy-hybrid rhenium adsorbent system with dual mechanisms and separation research from rhenium (VII)/copper (II) - Qian Cheng; Enming Luo; Lilin Gan; Wenzheng Luo; Dingfeng Yang; Hongquan Fu; Shuo Li (Journal of Water Process Engineering, 2025)

A baroduric immobilized composite material promoting remediation of oil-polluted sediment at typical deep-sea condition: The performances and potential mechanisms - Yanlu Qiao; Lingbing Kong; Mingan Shen; Yudi Sun; Shuo Wang; Yu Gao; Jianliang Xue; Qing Jiang; Dongle Cheng; Yuyang Liu (Environmental Research, 2025)

Highly sensitivity and wide-range flexible humidity sensor based on LiCl/cellulose nanofiber membrane by one-step electrospinning - Xiaomeng Liu; Lang Wang; Ying Lei; Xiao Li; Chunzu Cheng; Leixin Yang; Long Jiao; Shuo Yang; Dengkun Shu; Bowen Cheng (Chemical Engineering Journal, 2025)

Remediation of atrazine contaminated soil with the help of hydrothermal carbon/diatomite composite inoculated with degrading microorganisms - Tong Zhang; Hailing Yu; Zhaolian Han; Shuo Zhang; Jingjing Zhang; Shuang Xu; Zhihui Dong; Zhiqiang Cheng (Journal of Environmental Chemical Engineering, 2024)

Evaluating the thresholds for predicting post-earthquake debris flows: Comparison of meteorological, hydro-meteorological and critical discharge approaches - Zhen-lei Wei; Xuan-mei Fan; Jie Yang; Zong-shuo Zhang; Cheng-bin Zou (Engineering Geology, 2024)

Bacterial specialists playing crucial roles in maintaining system stability and governing microbial diversity in bioremediation of oil-polluted sediments under typical deep-sea condition - Yanlu Qiao; Wenhui Xu; Lingbing Kong; Mingan Shen; Shuo Wang; Yudi Sun; Yu Gao; Qing Jiang; Jianliang Xue; Dongle Cheng; Yuyang Liu (Bioresource Technology, 2024)

Roseomonas populi sp. nov., an acetate-degrading bacteria isolated from the stem of Populus tomentosa - Yao Cheng; Wen Zhu; Shuo Han; Jingjing Yang; Guanqi Wu; Guozhu Zhao; Xiangwei He (Antonie van Leeuwenhoek, 2024)

Engineering the interfacial hetero-structure for high-current-density hydrogen evolution - Bai Xu; Jiabin Xu; Junhui Hu; Shuo Li; Yong Feng; Cheng Lu; Kunming Hou; Lina Li; Kun Feng; Jun Zhong (Chemical Engineering Journal, 2024)

Sustainability assessment for China's intensive dairy farming: Integrating environmental and economic perspectives - Tianshu Xu; Tianzuo Zhang; Ziyue Cheng; Ziheng Li; Shuo Wang; Xinying Zhou; Changting Li; Liyao Wang; Mengqing Li; Jinglan Hong (Sustainable Production and Consumption, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

The Role of miRNA in Hyperthyroidism Induced by Excessive Iodine in Drinking Water - Zhihan Yang; Yishan Dong; Shuo Wang; Jing He; Zheng Shen; Jin Cheng; Jinyu Li; Qiaoling Liu; Ziqi Xu; Dianjun Sun; Wei Zhang (Biological Trace Element Research, 2024)

The research and application of technology and core components in commercial refrigeration and freezing Systems：A review - Hailing Fu; Shuo Huang; Yuan Li; Jiasen Cheng; Yang Guo; Kang Wang; Ranran Sun (Journal of Stored Products Research, 2024)

Unveiling the dynamics of co-created camping experiences: Influence of co-production on family cohesion and resilience via place identity - You-De Dai; Shih-Shuo Yeh; Minh Cong Nguyen; Chien-Wen Hung; Tzung-Cheng Huan (Journal of Outdoor Recreation and Tourism, 2024)

Evidence that microplastics at environmentally relevant concentration and size interfere with energy metabolism of microalgal community - Shuo Cheng; Kimleng Keang; Jeffrey S. Cross (Journal of Hazardous Materials, 2024)

Preparation of salicylic acid nano-protectant with dual synergistic mechanism: High direct fungicidal activity and plant defence toward cotton Verticillium wilt - Jiaming Yin; Jiajia Zhao; Zeng Wang; Fan Xue; Qi Wang; Huiming Guo; Hongmei Cheng; Jie Li; Jie Shen; Meizhen Yin; Xiaofeng Su; Shuo Yan (Chemical Engineering Journal, 2024)

High-efficiency metal-free CO2 mineralization battery using organic redox catalysts - Yunpeng Wang; Tao Liu; Chun Cheng; Yachen Xie; Cheng Lan; Wenchuan Jiang; Zhiyu Zhao; Shuo Zhai; Yiri Li; Yifan Wu; Heping Xie (Chemical Engineering Journal, 2024)

Bifunctional halloysite nanotube-based Ripk1 siRNA delivery system rescues cognitive impairment by targeting amyloid β plaques for clearance and reducing necrotic neurons in Alzheimer’s disease mice - Linmei Wu; Shuo Tan; Yizhu Yan; Lianghao Zhu; Zhaoyuan Wu; Zhihong Liu; Qiang Cheng; Qiuhao Qu; Xinyu Li; Qi Zhang; Jiayi Liu; Jun Chang; et al. (Chemical Engineering Journal, 2024)

Enhancing sludge hot-pressing drying by sawdust: Sensitivity analysis of heat and mass transfer physical properties of sludge, process performance, and kinetics - Dexiao Ma; Shuo Cheng; Guozhao Ji; Aimin Li (Process Safety and Environmental Protection, 2024)

Promoting sustainable potato production - Insights from an integrated life cycle environmental–economic assessment - Tianzuo Zhang; Changting Li; Shuo Wang; Ziyue Cheng; Ziheng Li; Tianshu Xu; Xinying Zhou; Wei Chen; Jinglan Hong (Agricultural Systems, 2024)

Arbuscular mycorrhizal fungi reduce soil N2O emissions by altering root traits and soil denitrifier community composition - Tangqing He; Wei Lin; Shuo Yang; Jiaqi Du; Bhoopander Giri; Cheng Feng; Frank S. Gilliam; Fuliang Zhang; Xiaoquan Zhang; Xuelin Zhang (Science of The Total Environment, 2024)

Pt/Al2O3 as efficient catalyst for the dehydrogenation of Dodecahydro-N-ethylcarbazole - Jihui Yao; Zhikang Xu; Shuo Cheng; Yuanyuan Yue; Haibo Zhu (Chemical Engineering Journal, 2024)

High-density mapping of durable and broad-spectrum stripe rust resistance gene Yr30 in wheat - Xiaoting Wang; Mingjie Xiang; Huaizhou Li; Xiaoxiao Li; Keqing Mu; Shuo Huang; Yibo Zhang; Xiangrui Cheng; Shuqing Yang; Xunying Yuan; Ravi P. Singh; Sridhar Bhavani; et al. (Theoretical and Applied Genetics, 2024)

The phytochemistry, pharmacology, pharmacokinetics, quality control, and toxicity of Forsythiae Fructus: An updated systematic review - Jin-Jin Li; Zi-Hao Chen; Cheng-Jun Liu; Yu-Shuo Kang; Xin-Pu Tu; Hong Liang; Wei Shi; Feng-Xiang Zhang (Phytochemistry, 2024)

Flash spinning polyethylene/Fe3O4 magnetic drive fibers for oil absorption underwater - Dengkun Shu; Xingyu Long; Pengju Zhao; Lang Wang; Zhenhua Li; Chunzu Cheng; Shuo Yang; Long Jiao; Peng Xi; Lei Xia; Chenyang Li; Bowen Cheng (Chemical Engineering Journal, 2024)

H5N1 high pathogenicity avian influenza virus in migratory birds exhibiting low pathogenicity in mallards increases its risk of transmission and spread in poultry - Qiuyan Mao; Zhixin Li; Yuecheng Li; Yaxin Zhang; Shuo Liu; Xin Yin; Cheng Peng; Rui Ma; Jinping Li; Guangyu Hou; Wenming Jiang; Hualei Liu (Veterinary Microbiology, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Effects of geometric structures on the sub-Kelvin porous media heat exchanger - Xue-shuo Shang; Han Gong; Xiao-xin Zeng; Bing-cheng Wang; Huai-qing Cao; Wei Shao; Zheng Cui (International Journal of Refrigeration, 2024)

In-situ electron capture by surface Co-Ci to facilitate the solar water splitting of Fe2O3 - Chang Li; Cheng Lu; Ye Zhu; Shuo Li; Yong Feng; Yiliu Yang; Bai Xu; Kun Feng; Jun Zhong (Chemical Engineering Journal, 2024)

Higher magnitude of sediment phosphorus release stimulated by ammonium than nitrate - Cheng Luo; Xu-Meng Dong; Shuo-Nan Ma (Journal of Soils and Sediments, 2024)

Study and application of deeply optimized neural network in roof stability evaluation - Huiyong Yin; Shuo Li; Guoliang Xu; Daolei Xie; Cheng Jiang; Fangying Dong; Houchen Wang; Bin Wu (Earth Science Informatics, 2024)

Relation between hydrophilic/hydrophobic characteristics of sludge extracellular polymeric substances and sludge moisture-holding capacity in hot-pressing drying - Dexiao Ma; Shuo Cheng; Yulin Zhang; Fahim Ullah; Guozhao Ji; Aimin Li (Science of The Total Environment, 2024)

Melatonin enhances cadmium tolerance in rice via long non-coding RNA-mediated modulation of cell wall and photosynthesis - Cheng-Wei Qiu; Marvin Richmond; Yue Ma; Shuo Zhang; Wenxing Liu; Xue Feng; Imrul Mosaddek Ahmed; Feibo Wu (Journal of Hazardous Materials, 2024)

Study on inverse geochemical modeling of hydrochemical characteristics and genesis of groundwater system in coal mine area – a case study of Longwanggou Coal Mine in Ordos Basin - Chang Lu; Wenju Cheng; Huiyong Yin; Shuo Li; Yian Zhang; Fangying Dong; Yuxiao Cheng; Xiaorong Zhang (Environmental Science and Pollution Research, 2024)

DNA methylation reprogramming mediates transgenerational diabetogenic effect induced by early-life p,p’-DDE exposure - Shuo Wang; Jingjing Wu; Zhong Chen; Wei Wu; Liping Lu; Yuzhou Cheng; Shuqi Li; Liangjing Chen; Xiaohua Tan; Lei Yang; Charles Wang; Yang Song (Chemosphere, 2024)

Evaluation of compost quality and the environmental effects of semipermeable membrane composting with poultry manure using sawdust or mushroom residue as the bulking agent - Shuo Liu; Jing-Li Zeng; Zeng-Wen Cheng; Jun-Liang He; Yan-Li Pang; Xin-Di Liao; Si-Cheng Xing (Journal of Environmental Management, 2024)

Influence of synthetic and natural microfibers on the growth, substance exchange, energy accumulation, and oxidative stress of field-collected microalgae compared with microplastic fragment - Shuo Cheng; Jessica; Kunio Yoshikawa; Jeffrey S. Cross (Science of The Total Environment, 2024)

Genome-wide profiling of genetic variations reveals the molecular basis of aluminum stress adaptation in Tibetan wild barley - Cheng-Wei Qiu; Yue Ma; Zi-Feng Gao; Jakkrit Sreesaeng; Shuo Zhang; Wenxing Liu; Imrul Mosaddek Ahmed; Shengguan Cai; Yizhou Wang; Guoping Zhang; Feibo Wu (Journal of Hazardous Materials, 2024)

LED-driven photocatalytic degradation of tetracycline by chromite ore processing residue (COPR): Mechanism, pathway, toxicity assessment - Shuo Zhang; Cunfang Lu; Yelei Wang; Cheng Tian; Peng Chen; Mingyuan Yang; Min Zhang; Rui Xu; Yuanyuan He; Zilong Li (Journal of Cleaner Production, 2024)

Texture and volatile profiles of beef tallow substitute produced by a pilot-scale continuous enzymatic interesterification - Shuo Zou; Jun Zhou; Yilin Du; Jianqiang Cheng; Yong Wang; Zhen Zhang (Food Chemistry, 2023)

Remediation of atrazine in environment by persulfate activation via N/B co-doped Si-rich biochar: Performance, mechanisms, degradation pathways and phytotoxicity - Tong Zhang; Hailing Yu; Zhaolian Han; Shuang Xu; Zhihui Dong; Kaishan Zhou; Shuo Zhang; Zhiqiang Cheng (Chemical Engineering Journal, 2023)

Zircon U–Pb geochronology, Hf–O isotopes and whole-rock geochemistry of A-type granitoids in Halajun, South Tienshan, NW China: Implications for subdivision, petrogenesis and tectonic settings - Tian-Chu Chen; Ming-Xing Ling; Yu-Long Liu; Ying Wei; Xi-Hui Cheng; Xiao-Yan Jiang; Shuo Xue; Ze-Bin Luo; Jiang-Hao Bai (Lithos, 2023)

Socio- and techno-economic analyses of biodiesel production from sewage sludge in Tokyo, Japan - Muhammad Usman; Shuo Cheng; Sasipa Boonyubol; Muhammad Aziz; Jeffrey S. Cross (Journal of Cleaner Production, 2023)

The effect of long-term controlled-release urea application on the relative abundances of plant growth-promoting microorganisms - Feng Gao; Zeli Li; Yongxiang Gao; E. Gaoyang; Mingyang Li; Chuanfu Li; Yunlong Cheng; Tianjiao Zhang; Shuo Wang; Liang Wu; Zhanbo Wei; Wenkui Zheng; et al. (European Journal of Agronomy, 2023)

Insight into the effect of a heavy metal mixture on neurological damage in rats through combined serum metabolomic and brain proteomic analyses - Jie Xie; Fankun Zhou; Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Shuo Yang; Jiajun Li; Xin Wan; Lingyu Yan; Peishan Liu; Hui Cheng; et al. (Science of The Total Environment, 2023)

Effects of virgin and BaP-adsorbed microplastics ingestion by Manila clams (Ruditapes philippinarum) - Jessica; Shuo Cheng; Jeffrey Scott Cross (Environmental Toxicology and Pharmacology, 2023)

Inactivation of SSIIIa enhances the RS content through altering starch structure and accumulating C18:2 in japonica rice - Yufeng Zhou; Zhenfeng Cheng; Shuo Jiang; Jinxi Cen; Siyuan Yuan; Chao Yu; Shaojie Huo; Ning Zhang; Dianxing Wu; Xiaoli Shu (Carbohydrate Polymers, 2023)

Anti-inflammatory, cardioprotective effect of gypenoside against isoproterenol-induced cardiac remodeling in rats via alteration of inflammation and gut microbiota - Xuemei Zhang; Ying Zhao; Xin Zhao; Ji Zhang; Jiayu Diao; Shuo Jia; Panpan Feng; Penghua Yu; Gong Cheng (Inflammopharmacology, 2023)

A new insight of water inrush mode and coal (rock) pillars setting in near-fault mining under high confined water - Fangying Dong; Huiyong Yin; Qingfu Feng; Shuo Li; Wei Zhou; Wenju Cheng; Mei Qiu; Yongli Shi; Chuanwei Jia (Journal of Applied Geophysics, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Genetic variability of rice stripe virus after its pandemic in Jiangsu - Chengye Lu; Qian Miu; Daoran Jin; Aiguo Li; Zhaobang Cheng; Yijun Zhou; Yunyue Wang; Shuo Li (Molecular Biology Reports, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

The effect of manure-borne doxycycline combined with different types of oversized microplastic contamination layers on carbon and nitrogen metabolism in sandy loam - Jing-Yuan Chen; Shuo Liu; Wei-Kang Deng; Shi-Hua Niu; Xin-Di Liao; Lei Xiang; Si-Cheng Xing (Journal of Hazardous Materials, 2023)

Achieving excellent energy storage performance at moderate electric field in Ca0.85Bi0.05Sm0.05TiO3-modified BiFeO3-based relaxor ceramics via multiple synergistic design - Shuo Liu; Wuwei Feng; Jinhong Li; Bin Tang; Cheng Hu; Yi Zhong; Bin He; Dengjie Luo (Chemical Engineering Journal, 2023)

Carbon-containing additives changes the phosphorus flow by affecting humification and bacterial community during composting - Shuxin Li; Shaoqi Xu; Shuo Chen; Hao Zhang; Yabin Zhan; Kaixue Jia; Meidi Cheng; Yuquan Wei (Bioresource Technology, 2023)

Biodiesel production from wet sewage sludge and reduced CO2 emissions compared to incineration in Tokyo, Japan - Muhammad Usman; Shuo Cheng; Jeffrey S. Cross (Fuel, 2023)

Erratum to: Dynamic response characteristics of a circular lined tunnel under anisotropy frost heave of overlying soil at the tunnel portal section in cold regions - Shuo-cheng Zhang; Wen-hua Chen (Journal of Mountain Science, 2023)

Dynamic model based integrated navigation for a small and low cost autonomous surface/underwater vehicle - Daxiong Ji; Huifang Cheng; Shuai Zhou; Shuo Li (Ocean Engineering, 2023)

Effects of the oversized microplastic pollution layer on soil aggregates and organic carbon at different soil depths - Shuo Liu; Shi-Hua Niu; Lei Xiang; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Dynamic response characteristics of a circular lined tunnel under anisotropy frost heave of overlying soil at the tunnel portal section in cold regions - Shuo-cheng Zhang; Wen-hua Chen (Journal of Mountain Science, 2023)

Bacillus subtilis pretreatment alleviates ethanol-induced acute liver injury by regulating the Gut-liver axis in mice - Shuo Wang; Jinqian Liu; Dong Cheng; Lehao Ren; Lixue Zheng; Fang Chen; Tao Zeng (Toxicology, 2023)

Improving the performance of nanogenerators via micro-capacitors and enhanced dipoles - Binbin Zhao; Lulu Lei; Yanfang Zhu; Zefei Cheng; Yansong Liu; Shuo Wang; Mingjia Liu; Tao Yu; Weidong Yang; Yan Li (Chemical Engineering Journal, 2023)

Genome sequence analysis of H7N3 subtype avian influenza virus originated from wild birds and its potential infectivity in mice - Xin Yin; Tiantian Wu; Cheng Peng; Jinping Li; Shuo Liu; Guangyu Hou; Wenming Jiang; Hualei Liu (Virus Genes, 2023)

Chemical investigations and cytotoxic effects of metabolites from Antrodia camphorata against human hepatocellular carcinoma cells - Yih-Fung Chen; Ho-Cheng Wu; Jia-Min Chang; Horng-Huey Ko; Chu-Hung Lin; Hsun-Shuo Chang (Natural Product Research, 2023)

The impact of heating rate on the decomposition kinetics and product distribution of algal waste pyrolysis with in-situ weight measurement - Muxuan Li; Ye Shui Zhang; Shuo Cheng; Boyu Qu; Aimin Li; Fandongkun Meng; Guozhao Ji (Chemical Engineering Journal, 2023)

Defective engineering and heteroatom doping construction in carbon nanobowls for achieving high-rate potassium-ion storage with long cyclic life - Jinbao Wang; Yanchao Qin; Longhui Li; Shuo Zhang; Xiangdong Pei; Zhulin Niu; Xiu-Cheng Zheng; Dan Li (Chemical Engineering Journal, 2023)

Doxycycline combined manure microbes to enhances biofilm formation of the soil plastisphere and increases the surface bio-risk of microplastics vehicle - Shuo Liu; Wei-Kang Deng; Shi-Hua Niu; Chun-Hao Mo; Xin-Di Liao; Si-Cheng Xing (Chemical Engineering Journal, 2023)

Separation of a new triterpenoid saponin together with six known ones from Clematis tangutica (Maxim.) Korsh and evaluation of their cytotoxic activities - Yangfei Wei; Tao Chen; Shuo Wang; Cheng Shen; Shuping Yan; Zhibo Song; Yarong Liu; Fengmei Yang; Ping Hai; Yulin Li (Natural Product Research, 2023)

Spatiotemporal variations of tidal flat landscape patterns and driving forces in the Yangtze River Delta, China - Shuo Cheng; Xu Zeng; Zihan Wang; Cong Zeng; Ling Cao (Frontiers in Marine Science, 2023)
As a crucial coastal wetland habitat in the transition zone between land and sea, global tidal flats have severely declined by 16% over the last two decades under the dual threats of intense human activities and climate change. The Yangtze River Delta of China, the largest estuary in the western Pacific Ocean, has abundant mudflat resources and a dense human population. It also has some of the most prominent conflicts between economic development and ecological conservation. The current lack of understanding of landscape patterns and influencing factors of the Yangtze River Delta mudflats has severely hampered the region’s ecological conservation and restoration efforts. Based on Landsat time-series images, this study generated a 30-m spatial resolution map of mudflats in the Yangtze River Delta, which shrank by 47% during 1990–2020, with a higher density of mudflat loss in Yancheng and Nantong cities of the Jiangsu province and Hangzhou, Shaoxing, and Ningbo cities of the Zhejiang province. Landscape indices, such as the patch density of tidal flats, have gradually changed since 2000, with most of them showing significant changes in 2010. Mudflats in Lianyungang, northwestern Yancheng, Nanhui, Jiaxing, and Hangzhou showed sharp negative changes in landscape characteristics. Natural and anthropogenic factors had synergistic effects on the above changes in mudflat landscape patterns in the Yangtze River Delta. Mudflat landscape features were mainly influenced by population growth, economic development, reclamation, sediment discharge, and air temperature. Based on the evolving characteristics of mudflat landscape patterns, we recommend improving mudflat landscape management and planning by strengthening mudflat policies, laws, and regulations, developing countermeasures against threats from major stressors, and enhancing the effectiveness of nature reserves for mudflat protection.

Study on the trajectory of tip leakage vortex and energy characteristics of mixed-flow pump under cavitation conditions - Wei Li; Mingjiang Liu; Leilei Ji; Shuo Li; Rui Song; Cheng Wang; Weidong Cao; Ramesh K. Agarwal (Ocean Engineering, 2023)

Achieving high energy storage density and efficiency simultaneously in Sr(Nb0.5Al0.5)O3 modified BiFeO3 based lead-free ceramics - Shuo Liu; Wuwei Feng; Jinhong Li; Changchun Zhao; Cheng Hu; Bin He; Zhidi Bao; Xuezhu Luan (Chemical Engineering Journal, 2023)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

Monthly runoff prediction by a multivariate hybrid model based on decomposition-normality and Lasso regression - Yan Kang; Xiao Cheng; Peiru Chen; Shuo Zhang; Qinyu Yang (Environmental Science and Pollution Research, 2022)

Age, Growth and Maturation of Largehead Hairtail (Trichiurus japonicus) in the East China Sea - Shuo Cheng; Peng Sun; Yang Liu; Qi Chen; Zhengtong Shi; Runlong Sun (Journal of Ocean University of China, 2022)

Integrated Analyses of miRNome and Transcriptome Reveal the Critical Role of miRNAs Toward Heat Stress Response in Isochrysis galbana - Jia-Yi Cao; Si-Min Xu; Ying-Ying Wang; Xie-Dan Long; Shuo-Nan Ma; Cheng-Xu Zhou; Ji-Lin Xu; Xiao-Jun Yan (Marine Biotechnology, 2022)

Allergy from perspective of environmental pollution effects: from an aspect of atopic dermatitis, immune system, and atmospheric hazards—a narrative review of current evidences - Su Boon Yong; Shuo-Yan Gau; Yu-Chen Guo; James Cheng-Chung Wei (Environmental Science and Pollution Research, 2022)

Nitrogen Enrichment Reduces the Diversity of Bacteria and Alters Their Nutrient Strategies in Intertidal Zones - Yuan-Feng Xu; Xu-Meng Dong; Cheng Luo; Shuo-Nan Ma; Ji-Lin Xu; Yong-De Cui (Frontiers in Marine Science, 2022)
Intertidal ecosystems are affected by severe nitrogen (N) pollution as a result of anthropogenic activities, and it is unclear how this may affect intertidal microbial communities, which play critical roles in regulating biogeochemical cycles. To address this gap, we conducted a two-month mesocosm experiment using six targeted concentrations of total N. The findings indicated that N entering seawaters has direct negative effects on the bacterial diversity. Dose dependence was found for the effects of N on bacterial diversity in sediment: low N addition increased the bacterial diversity, but a reduction in bacterial diversity occurred when N exceeded a certain value (≥ 3 mg L−1). Additionally, N enrichment caused clear shifts in bacterial community composition with increases in the relative abundance of Balneola (organic-degrading), Phalacroma mitra (carbohydrate-fermenting), and Bacteroides (phosphorus (P)-solubilizing), and decreases in Leptolyngbya_PPC_6406 (N2-fixing). The increased abundance in P-solubilizing and organic-degrading bacteria and decrease in N-fixing bacteria, combined with the upregulated activity of alkaline phosphatase and downregulation of urease activity, implied that the bacterial assemblage tended to be more effective in P and carbon acquisition but reduced N acquisition. Further path analysis suggested that N had direct effects on bacteria and contributed 50%–100% to the variations in bacterial diversity, whereas environmental changes such as dissolved oxygen and pH played minor roles. Overall, bacteria occurring in sediment were likely more stress-resistant to high N exposure than those occurring in seawater, possibly due to the high buffering capacity of sediment and growth tolerances of bacteria in the sediment. These findings point to the vulnerability of microbes in water systems to increasing global N loading, and that N reduction is needed to combat the loss of microbial diversity.

Quantifying soil nitrous oxide emissions in spring freezing-thawing period over different vegetation types in Northeast China - Bin Wu; Chang-cheng Mu; Hui Liu; Ya-kun Xu; Yue Zhang; Jia-shuo Yang; Wen-nian Xu (Journal of Mountain Science, 2022)

Superior degradation of phenolic contaminants in different water matrices via non-radical Fenton-like mechanism mediated by surface-disordered WO3 - Ai-Yong Zhang; Shuo Xu; Jing-Wei Feng; Pin-Cheng Zhao; Heng Liang (Environmental Science and Pollution Research, 2022)

Migration and abiotic transformation of estrone (E1) and estrone-3-sulfate (E1-3S) during soil column transport - Banghao Du; Weiwei Yu; Lun Yang; Gongduan Fan; Shuo Yang; Hui Jiang; Shenglan Bi; Cheng Yu (Environmental Geochemistry and Health, 2022)

A comprehensive exploration on pollution characteristics and health risks of potentially toxic elements in indoor dust from a large Cu smelting area, Central China - Han-Zhi Wang; Li-Mei Cai; Shuo Wang; Guo-Cheng Hu; Lai-Guo Chen (Environmental Science and Pollution Research, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Low-Se Diet Can Affect Sperm Quality and Testicular Glutathione Peroxidase-4 activity in Rats - Qin Wang; Shuo Zhan; Yiqun Liu; Feng Han; Lili Shi; Chao Han; Weipeng Mu; Jizhong Cheng; Zhen-wu Huang (Biological Trace Element Research, 2021)

Development of a dual-labeled, hydrolysis probe-based, real-time quantitative PCR assay for detection of both genotypes of duck circovirus-1 (DuCV-1) and DuCV-2 - Lin Zhang; Wenming Jiang; Fuyou Zhang; Yang Li; Jinping Li; Shaobo Liang; Xiaohui Yu; Cheng Peng; Shuo Liu; Jingjing Wang; Shuhong Sun; Hualei Liu (Virus Genes, 2021)

Patient Confidential Information Transmission Using the Integration of PSO-Based Biomedical Signal Steganography and Threshold-Based Compression - Shih-Ying Chen; Shan-Ju Lin; Ming-Cheng Tsai; Ming-Dar Tsai; Yih-Jing Tang; Shuo-Tsung Chen; Li-Hsiang Wang (Journal of Medical and Biological Engineering, 2021)

Comparison of 1-D analytical solutions and a numerical model for quantifying hyporheic exchange flux using the temperature tracer method - Wenbing Zhang; Zhenzhong Shen; Jie Ren; Jiaqiang Cheng; Yijun Wu; Shuo Wang (Arabian Journal of Geosciences, 2021)

On the ~ 7 year periodic signal in length of day from a frequency domain stepwise regression method - Can-Can Hsu; Peng-Shuo Duan; Xue-Qing Xu; Yong-Hong Zhou; Cheng-Li Huang (Journal of Geodesy, 2021)
The intradecadal variations in length-of-day (LOD) and their time-varying characteristics still need to be further studied. Given that the corresponding signal periods on the intradecadal scales are quite close to each other and the span of currently observed ΔLOD data (i.e., 1962–2019, only 57 years) is not long enough, accurate detection of these signals depends on using effective mathematical method. On the basis of the traditional harmonic retrieval model, this work proposes a frequency domain stepwise regression method, which can well identify the periodic components with close periods and recognize the weaker signals to estimate the relevant harmonic parameters (i.e., amplitude, frequency and phase). Furthermore, we apply this method to detection of the actual LOD intradecadal variations, the result of which shows that there are three components (i.e., the ~ 5.9 years, ~ 8.3 years and ~ 7.3 years) existing in LOD intradecadal variations. Here, we firstly give the time-domain harmonic expression of the ~ 7.3 years signal, i.e., $$y\left(t\right)=Acos\left(\frac{2π }{T}\left(t-1962+ψ \right)\right)$$ y t = A cos 2 π T t - 1962 + ψ , where the period $$T=7.33$$ T = 7.33 years, amplitude $$A=0.0413(± 0.0099)$$ A = 0.0413 ( ± 0.0099 ) ms, phase $$ψ =-1.58(± 0.30)$$ ψ = - 1.58 ( ± 0.30 ) years. The mechanism of this ~ 7.3 years signal needs to be further studied.

A Simplified Calculation Method for Vertical Displacement of Shield Tunnel Caused by Adjacent Excavation - Riqing Xu; Shuo Shen; Mei Dong; Kang Cheng (Geotechnical and Geological Engineering, 2021)

Yarrowia lipolytica as an emerging biotechnological chassis for functional sugars biosynthesis - Muhammad Bilal; Shuo Xu; Hafiz M. N. Iqbal; Hairong Cheng (Critical Reviews in Food Science and Nutrition, 2021)

A Visual Analysis Approach to Understand and Explore Quality Problems of AIS Data - Wei He; Jinyu Lei; Xiumin Chu; Shuo Xie; Cheng Zhong; Zhixiong Li (Journal of Marine Science and Engineering, 2021)
Low quality automatic identification system (AIS) data often mislead analysts to a misunderstanding of ship behavior analysis and to making incorrect navigation risk assessments. It is therefore necessary to accurately understand and judge the quality problems in AIS data before a further analysis of ship behavior. Outliers were filtered in the existing methods of AIS quality analysis based only on mathematical models where AIS data related quality problems are not utilized and there is a lack of visual exploration. Thus, the human brain’s ability cannot be fully utilized to think visually and for reasoning. In this regard, a visual analytics (VA) approach called AIS Data Quality visualization (ADQvis) was designed and implemented here to support evaluations and explorations of AIS data quality. The system interface is overviewed and then the visualization model and corresponding human-computer interaction method are described in detail. Finally, case studies were carried out to demonstrate the effectiveness of our visual analytics approach for AIS quality problems.

Detection of wind corridors based on “Climatopes”: a study in central Ji’nan - Yonghong Liu; Pengfei Cheng; Peng Chen; Shuo Zhang (Theoretical and Applied Climatology, 2020)

Complex magma sources of late Mesozoic granites along the southern margin of the North China Craton: constraints from geochemistry and geochronology of the massive Heyu and Lantian plutons - Yan Wang; Yuan-Shuo Zhang; Hong Cheng; Fukun Chen (International Geology Review, 2020)

Comparing Subsurface Seasonal Deoxygenation and Acidification in the Yellow Sea and Northern East China Sea Along the North-to-South Latitude Gradient - Tian-qi Xiong; Qin-sheng Wei; Wei-dong Zhai; Cheng-long Li; Song-yin Wang; Yi-xing Zhang; Shuo-jiang Liu; Si-qing Yu (Frontiers in Marine Science, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

Dopamine D2 Receptor-Mediated Modulation of Rat Retinal Ganglion Cell Excitability - Ning Yin; Yu-Long Yang; Shuo Cheng; Hong-Ning Wang; Xin Hu; Yanying Miao; Fang Li; Zhongfeng Wang (Neuroscience Bulletin, 2020)

Secondary metabolites from the fermented rice of the fungus Monascus purpureus and their bioactivities - Ho-Cheng Wu; Ming-Jen Cheng; Ming-Der Wu; Jih-Jung Chen; Yen-Lin Chen; Hsun-Shuo Chang; Kai-Ping Chen (Natural Product Research, 2019)

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

Neferine inhibits LPS-ATP-induced endothelial cell pyroptosis via regulation of ROS/NLRP3/Caspase-1 signaling pathway - Yang-Shuo Tang; Yan-Hua Zhao; Yong Zhong; Xiao-Zhao Li; Jia-Xi Pu; Yan-Cheng Luo; Qiao-Ling Zhou (Inflammation Research, 2019)

Implementation of an Environmental Quality and Harmful Gases Monitoring System in Cloud - Chao-Tung Yang; Shuo-Tsung Chen; Chih-Hung Chang; Walter Den; Chia-Cheng Wu (Journal of Medical and Biological Engineering, 2019)

Metals in wild fish from Gaotang Lake in the area of coal mining, China: assessment of the risk to human health - Jiali Cheng; Xianhui Zhang; Shuo Ren; Tonglei Wang; Zhenwu Tang (Environmental Science and Pollution Research, 2019)

Skipping of an exon with a nonsense mutation in the DMD gene is induced by the conversion of a splicing enhancer to a splicing silencer - Yanrong Zhu; Huiting Deng; Xiangfa Chen; Hui Li; Cheng Yang; Shuo Li; Xiaoying Pan; Siqi Tian; Shuxin Feng; Xiaoyue Tan; Masafumi Matsuo; Zhujun Zhang (Human Genetics, 2019)

Rac1 Modulates Excitatory Synaptic Transmission in Mouse Retinal Ganglion Cells - Ling-Zhu Li; Ning Yin; Xue-Yan Li; Yanying Miao; Shuo Cheng; Fang Li; Guo-Li Zhao; Shu-Min Zhong; Xin Wang; Xiong-Li Yang; Zhongfeng Wang (Neuroscience Bulletin, 2019)

Chimeric GII.3/GII.6 norovirus capsid (VP1) proteins: characterization by electron microscopy, trypsin sensitivity and binding to histo-blood group antigens - Shuhuan Ma; Lijun Zheng; Jinjin Liu; Wenhui Wang; Jie Ma; Xuhui Cheng; Lili Ge; Mingchen Wang; Yuqi Huo; Shuo Shen (Archives of Virology, 2018)

Facultative production of multiple-egg clutches in a quasi-gregarious parasitoid: fitness gains for offspring at low developmental temperature - Peng-Cheng Liu; Ju Luo; Shuo Tian; Shao-Ying Wen; Jian-Rong Wei; De-Jun Hao (Behavioral Ecology and Sociobiology, 2018)

GPR30 Activation Contributes to the Puerarin-Mediated Neuroprotection in MPP+-Induced SH-SY5Y Cell Death - Yue-Fa Cheng; Guoqi Zhu; Qing-Wen Wu; Yue-Sheng Xie; Yan Jiang; Lan Guo; Ya-Li Guan; Ying-Shuo Liu; Jun Zhang (Journal of Molecular Neuroscience, 2017)

Mechanical Testing of Tomato Plant Stem in Relation to Structural Composition - Xiliang Zhang; Qian Guo; Yunfeng Xu; Pingping Li; Cheng Chen; Shuo Wu (Agricultural Research, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

Gas desorption index of drill cuttings affected by magmatic sills for predicting outbursts in coal seams - Long-biao Cheng; Liang Wang; Yuan-ping Cheng; Kan Jin; Wei Zhao; Li-shuo Sun (Arabian Journal of Geosciences, 2016)

Ketamine-Induced Toxicity in Neurons Differentiated from Neural Stem Cells - William Slikker; Fang Liu; Shuo W. Rainosek; Tucker A. Patterson; Natalya Sadovova; Joseph P. Hanig; Merle G. Paule; Cheng Wang (Molecular Neurobiology, 2015)

Amanita subpallidorosea, a new lethal fungus from China - Hai-Jiao Li; Jian-Wei Xie; Shuo Zhang; Ya-Juan Zhou; Pei-Bin Ma; Jing Zhou; Cheng-Ye Sun (Mycological Progress, 2015)

PAHs in sediment cores at main river estuaries of Chaohu Lake: implication for the change of local anthropogenic activities - Chen Ren; Yaketon Wu; Shuo Zhang; Liang-Liang Wu; Xiao-Guo Liang; Tian-Hu Chen; Cheng-Zhu Zhu; Samuel O Sojinu; Ji-Zhong Wang (Environmental Science and Pollution Research, 2015)

Identification of a potential novel type of influenza virus in Bovine in China - Wen-Ming Jiang; Su-Chun Wang; Cheng Peng; Jian-Min Yu; Qing-Ye Zhuang; Guang-Yu Hou; Shuo Liu; Jin-Ping Li; Ji-Ming Chen (Virus Genes, 2014)

Synthesis and analgesic evaluation of a series of proline-typed spiro cyclic quaternary ammoniums - Songwen Lin; Na Wang; Shuo Zhao; Qi Sun; Weiwei Zhang; Jia Ye; Tieming Cheng; Runtao Li (Medicinal Chemistry Research, 2014)

Genetic diversity and relationships of common apricot (Prunus armeniaca L.) in China based on simple sequence repeat (SSR) markers - Qiu-Ping Zhang; Dong-Cheng Liu; Shuo Liu; Ning Liu; Xiao Wei; Ai-Min Zhang; Wei-Sheng Liu (Genetic Resources and Crop Evolution, 2014)

Biocatalytic characterization of a short-chain alcohol dehydrogenase with broad substrate specificity from thermophilic Carboxydothermus hydrogenoformans - Shuo Zhou; Shun-Cheng Zhang; Dun-Yue Lai; Shuang-Ling Zhang; Zhen-Ming Chen (Biotechnology Letters, 2013)

Genetic diversity of sweet potato begomoviruses in the United States and identification of a natural recombinant between sweet potato leaf curl virus and sweet potato leaf curl Georgia virus - Shuo Cheng Zhang; Kai-Shu Ling (Archives of Virology, 2011)

Alternative splicing of the FGF antisense gene: differential subcellular localization in human tissues and esophageal adenocarcinoma - Shuo Cheng Zhang; Christie Barclay; Leigh Ann Alexander; Laurette Geldenhuys; Geoffrey A. Porter; Alan G. Casson; Paul R. Murphy (Journal of Molecular Medicine, 2007)